RELIABILITY OF THE FOLDING MODEL IN DESCRIBING THE ELASTIC SCATTERING OF SOME HALO NUCLEI - ISMAIL AHMED, ATEF FATHY (2018)
This work devoted to study the heavy ions including the stable nuclei, exotic nuclei ‘Halo Nuclei’ and much stable nuclei ‘Doubly–Magic Nuclei’. The second type contains two classes of the nuclear halo nuclei, neutron halo and proton halo. This study concentrates on the neutron halo nuclei: 15;17;19C and 11Be; and the 16;22C, 6He and 11Li. The first group has one neutron–halo whereas the second group has two neutron– halo. In the last three decades, since Tanihata’s research group discovered the halo phenomenon in the exotic nucleus 11Li, a stream of studies tried to reveal the ambiguities on this type of exotic nuclei.